Experimental study of the impact of trace amounts of acetylene and methylacetylene on the synthesis, mechanical and thermal properties of polypropylene (2022)
During the production of polymer-grade propylene, different processes are used to purify this compound and ensure that it is of the highest quality. However, some impurities such as acetylene and methyl acetylene are difficult to remove, and some of these impurities may be present in the propylene used to obtain polypropylene, which may have repercussions on the process. This study evaluates the impact of these acetylene and methyl acetylene impurities on the productivity of the polypropylene synthesis process and on the mechanical and thermal properties of the material obtained through the synthesis of eight samples with different concentrations of acetylene and eight samples with different concentrations of acetylene. We discovered that for the first concentrations of both acetylene (2 and 3 ppm) and methyl acetylene (0.03 and 0.1), the MFI, thermal recording, and mechanical properties of the resin were unaffected by the variation of the fluidity index, thermal degradation by TGA, and mechanical properties such as resistance to tension, bending, and impact. However, when the concentration exceeded 14 ppm for methyl acetylene and 12 ppm for acetylene, the resistance of this resin began to decrease linearly. Regarding production, this was affected by the first traces of acetylene and methyl acetylene progressively decreasing.